Decreased platelet inhibition by P2Y12 receptor blockers in anaemia. (7th December 2017) - Wadowski, Patricia P.; Kopp, Christoph W.; Koppensteiner, Renate; Lang, Irene M.; Pultar, Joseph; Lee, Silvia; Weikert, Constantin; Panzer, Simon; Gremmel, Thomas
Abstract: Background: Anaemic patients undergoing angioplasty and stenting are at an increased risk of ischaemic events, which may be caused by an inadequate response to antiplatelet therapy with adenosine diphosphate (ADP) P2Y12 inhibitors. In the current study, we investigated the associations between anaemia and on‐treatment platelet reactivity in clopidogrel‐treated (group 1, n = 306) and prasugrel‐/ticagrelor‐treated (group 2, n = 109) patients undergoing elective and acute angioplasty with stent implantation, respectively. Materials and methods: Monocyte‐platelet aggregate (MPA) formation was determined by flow cytometry in both groups. On‐treatment residual platelet reactivity in response to ADP was assessed by light transmission aggregometry (LTA) in both groups, and by the VerifyNow P2Y12 assay and the Impact‐R in group 1. P‐selectin expression was measured by flow cytometry in group 2. Results: In both groups, anaemia was associated with significantly higher MPA formation in response to ADP (both P  ≤ .02). Moreover, by LTA maximal aggregation in response to ADP was significantly higher in patients with anaemia in both groups (both P  < .05), and anaemic patients in group 1 had a significantly higher on‐treatment platelet reactivity by the VerifyNow P2Y12 assay and the Impact‐R than those without anaemia (both P  < .001). In group 2, significantly higher platelet surface expression of P‐selectin was seen in anaemia after stimulation with ADP ( P  = .02). Conclusion: Anaemia is associated with decreased platelet inhibition by ADP P2Y12 receptor antagonists after elective and acute percutaneous interventions with stent implantation. However, due to inconsistencies between different platelet function tests additional data are needed to clarify the role of anaemia for platelet inhibition.